Transformational Leadership in Military Organization to Supporting National Defense Capability in Era of Industrial Revolution 4.0: A Literature Review - Dyah Anissa Rehardiningtyas; Hikmat Zakky Almubaroq (Faculty of Social Science, Universitas Negeri Padang, 2021)
TNI as a means of state defence is who in charge to carrying out state defence to uphold state sovereignty, maintain territorial integrity, and protect the safety of the nation. For military organizations, leadership is the main thing needed, every military soldier is always ready to carry out orders from superiors, leadership attitudes to defend and develop themselves personally are very much needed both in everyday life or during combat. Transformational leadership is characterized by a leader working with subordinates to identify needed change, creating a vision to guide change through inspiration, and implementing the change together with committed group members. This study uses a descriptive qualitative approach as the main writing approach. The data used in this paper is secondary data. A transformational leader will be able to make positive changes in the organization. Transformational leadership in the industrial era 4.0 generates commitment from all stakeholders involved and increases the satisfaction and trust of everyone involved in the organization. The conclusion in the study: a good TNI leadership model is a transformational leadership model that emphasizes a leader motivating his subordinates to carry out responsibilities